Emancipatory Human Rights and the University : Promoting Social Justice in Higher Education - Tibbitts, Felisa; Keet, André (Routledge research in higher education, 2024)
"This volume explores the application of human rights to higher education through a critical lens. Combining theoretical and applied perspectives, it asks what a human rights framework grounded in liberation and justice can offer to ways of working and teaching practices in higher education. Human rights, in this edited compilation, call for continuous critical engagements around the higher education transformation project. The book recognizes human rights simultaneously as law, values, and emancipatory vision. It showcases global north and global south perspectives and encourages a dialogue between the human rights approach and other approaches to higher education transformation, such as decolonialisation, anti-racism, diversity and inclusion, and intersectionality. Individual chapters featuring a range of case studies written from global south and north perspectives critically examine higher education practices linked with human rights, ranging from curricular practices to student activism and community partnerships; the critical space of the university and its role in the transformation of society is therefore viewed in multi-dimensional ways. Underlining the value of applying human rights as a framework in understanding and designing higher education transformation, the book will be of great interest to scholars, researchers, and post-graduate students in the fields of the sociology of education, human rights education, higher education and social justice education"